Measuring Emotional Intelligence of Islamic Higher Education Students: A Factor Analysis Approach - Firdaos, Rijal; Mustofa, Muhammad (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2023)
According to many studies, emotional intelligence is a crucial factor that can contribute to the success of the academic and non-academic domains. This research aimed to assess the emotional intelligence of Islamic students in higher education. The participants in this research were 151 Islamic higher education students. The researcher employed the survey technique with Likert scale parameters. This research empirically states that 39 emotional intelligence measuring instruments were spread into five dimensions. The construct validity results using factor analysis showed that the items that had been successfully estimated were 39 indicators that were higher than 0.50. Of the 56 items, 14 items were invalid based on the MSA value in stage one, namely items 1, 2, 4, 6, and 7 on the understanding self-emotions dimensions, item 24 on the managing self-emotions dimensions, items 25 and 34 on the self-motivation dimensions, and items 36, 39, 40, 41, 42, and 43 on the building relationships with other people dimensions. Furthermore, for understanding other people's emotions, all of the items’ MSA values were above 0.5. In the second stage, the assessment was based on the loading factor. Three items were invalid because they did not meet the requirements. The three items were item 1 of the understanding self-emotions dimension, items 10 and 13 on managing self-emotions dimensions. For the other three dimensions, all of the items’ loading factors were higher than 0.50. Likewise, the reliability index in the first stage was 0.761, and the reliability index in the second stage was 0.817 (both indexes were higher than 0.70). Therefore, the emotional intelligence instrument could be declared reliable.